Heydar Aliyev as a Leader for Azerbaijan and the Whole World. Review of the book by Sadig Gurbanov “A leader transcending time. Heydar Aliyev’s governance and succession philosophy” - O. V. Belova (Informaciâ i Innovacii)
.